The development of the reaction in children who are engaged in football taking into account their nervous system - Georgy Georgievich Polevoy (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2018)
In this study, we investigated the effect of typological peculiarities of manifestations of properties of the nervous system of young football players the ability to react quickly. 32 young football players of 10-11 years participated in the pedagogical experiment. 16 athletes were engaged in experimental methodic which is based on using the same exercise and methods development of the ability to react quickly, but different components of the load, for players with a strong nervous system (8 people), the load was intensive, but for players with a weak nervous system (8 persons) - volumetric load. The other 16 football players made up the control group. For 8 months of the experiment there was a significant increase in the ability to react quickly football players 10-11 years old in the experimental group, which was engaged in by a special methodic. The football players with a strong nervous system indicator has improved from 251.4 ± 4.6 cm to 231.4 ± 5.9 cm (P<0.05), and football players with a weak nervous system - from 252.9 ± 4.2 cm to 234.3 ± 8.1 cm (P<0.05). In the control group also occurred the positive, but not significant changes (P> 0.05). The study proved the effectiveness of the use of the typological properties of the nervous system as a differentiated method of developing the ability to react quickly of young football players. This approach allows to improve the quality of the training process of young athletes.   RESUMO O desenvolvimento da reação em crianças que estão envolvidas no futebol levando em conta o sistema nervoso Neste estudo, nós investigamos o efeito das peculiaridades tipológicas de manifestações de propriedades do sistema nervoso de jovens jogadores de futebol a capacidade de reagir rapidamente. 32 jovens jogadores de futebol de 10-11 anos, participaram na experiência pedagógica. 16 atletas foram contratados experimental metódica, que é baseado no uso de um mesmo exercício e métodos de desenvolvimento da capacidade de reagir rapidamente, mas diferentes componentes da carga, para os jogadores com um forte sistema nervoso (8 pessoas), a carga foi intenso, mas, para os jogadores com um fraco sistema nervoso (8 pessoas) - volumétrica de carga. Os outros 16 jogadores de futebol compõem o grupo de controle. Durante 8 meses do experimento, houve um aumento significativo na capacidade de reagir rapidamente os jogadores de futebol 10-11 anos de idade no grupo experimental, o qual foi contratada, em especial metódica. Os jogadores de futebol com um forte sistema nervoso indicador melhorou de 251,4 ± 4,6 cm para 231,4 ± 5,9 cm (P<0,05), e os jogadores de futebol com um fraco sistema nervoso - a partir de 252,9 ± 4,2 cm para 234,3 ± 8,1 cm (P<0,05). No grupo de controlo também ocorreu o positivo, mas não alterações significativas (P> 0,05). O estudo comprovou a eficácia da utilização do tipológicas propriedades do sistema nervoso como um método diferenciado de desenvolver a capacidade de reagir rapidamente de jovens jogadores de futebol. Esta abordagem permite melhorar a qualidade do processo de formação de jovens atletas.